تکریم انسانیت: اسلام اور ہندو مت کا مطالعہ - Rai Usman Abbas; Hafiz Zahid Latif (Mujalla Islami Fikr-o-Tahzeeb (MIFT) / مجلہ اسلامی فکر و تہذیب, 2022)
Allah Almighty has created man with honor, respect and reverence and taught us to treat others similarly. Every religion has laid down its own set of rules for respecting humanity. In addition, it is essential that humans must respect other humans. When a child gain consciousness after birth, he/she associate and adapts to a particular religion of their parents or through their environment. The fundamental principles of that religion are very essential to him/her in conducting and regulating matters of life. Due to this reason, mankind learns the teachings of his religion and try to incorporate those in their lives as laws and legislations. In this paper, we are going to compare and contrast the teachings of Islam (a monotheistic religion) and Hinduism (a polytheistic religion) in terms of respecting humanity. Where Islam preach concepts like equality among human beings, fair distribution of inheritance, rights of humans superseding over the rights of Allah, women rights and the concept of salvation etc. On the contrary, Hinduism endorses division of caste, recognizing Brahmans as sacred, cruelty to Shudras, the concept of metempsychosis and inequitable distribution of inheritance etc. This paper aims to study the disparities in minute detail. Keywords: Humanity, Respect, Dignity, Islam, Hinduism